Disponibilite, Valeurs Marchande Et Nutritionnelle Des Sous-Produits Agricoles Et Agroindustriels Utilises Dans L’alimentation Des Ruminants Au Benin - M., Montcho; S., Babatoundé; B. A., Aboh; M. J. D., Bahini; A. A. M. C., Chrysostome; G. A., Mensah (European Scientific Journal, ESJ, 2016)
The availabilities and the commercial values of 31 agricultural and agro-industrial by-products were evaluated through a semi structural interview carried out on 360 breeders of Benin. A sample of each diet was collected to determine its chemical composition and nutritive values. Maize bran, cassava peels, cakes of soya and cotton are available in any season and have a commercial value. Among fruit by-products used in the food of the ruminants, the pineapple peels occupy the first place and their commercial values are three times higher than those of the cassava peels. Soya cakes has a very high commercial value (higher than 200 FCFA/kg).The leguminous pods and the cereal hulls are also largely available but without commercial value. Roots cassava and tubers of yam by-products and the cakes are very digestible and these values do not go down below 60 %. Low values of digestibility were observed on hulls and stems of cereals and leguminous pods. These digestibilities are generally below 40 %. The groundnut haulms are more digestible than cowpea haulms (57.8 vs 49.7 %). Cotton cakes and palm oil cakes are less digestible than the other oil cakes. The digestibilities of crude protein (DCP) are very low in fruit and cereals by-products. Except for the pods of leguminous, all the leguminous by-products provided considerable quantities in DCP. The studies give opportunities of choice of food supplementation to ruminants during the dry season where graminaceous and the other herbaceous becoming rare in the natural pasture.